A Kinetic and Kinematic Study for Plane Pantograph Machine - Abo Hatem, Ahmad Hatem Taj Al Deen; Hasan, Mustafa Rafeek (Journal of natural sciences, life and applied sciences, 2019)
The plane pantograph machine is considered as a significant one which has its own missions including figures copying, sculptural and minting works, and geometric properties such homothety.Moreover, achieving simple mathematical operations such determining the midpoint of a straight line segment with knowing its end points, adding two complex numbers,.. etc.Then, we found a new type of pantograph machine which can make many copies for some figures desired to copied with different magnification factors.Because of the importance of this machine we liked to kinetic and kinematic study about this machine then determining plane domain which this machine can work in and distinguishing two basic positions for this machine.
Keywords: planar mapping machine; geometric properties; mathematical operations